The geomorphic landscape of the Barva volcano, Costa Rica - Quesada Román, Adolfo (2020)
Volcanoes have a beneficial role in human development; however, this balance could turn to hazardous processes or even environmental disturbances. Costa Rica is a volcanic country. The people of Costa Rica live upon these landscapes and take advantage of the benefits afforded, such as water recharge, the fertile soils for agriculture purposes, and world-renowned ecological tourism. The Barva volcano is a complex andesitic shield located in the Central Volcanic Range of Costa Rica. Its southern slopes bound the Greater Metropolitan Area (GAM) that contains 65% of the country’s population. We performed a geomorphic landscape analysis which delineated seven landforms that consider the climatic, edaphic, hydrologic, and land use characteristics that describe the largest volcanic massif in Central America. This work is a basic input for environmental, disaster risk, and land use planning for tropical volcanic landscapes under urban and rural pressures. This methodology could facilitate the natural resources management in developing countries where baseline information is scarce.